2008
DOI: 10.1007/s10692-008-9023-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyhydroxybutyrate coating on the characteristics of surgical knots in lavsan sutures

Abstract: A comparative study of the characteristics of surgical knots in the initial lavsan thread and sutures with a coating of the biocompatible and biodegradable polymer polyhydroxybutyrate showed that modification did not reduce the holding power, effectiveness, and degree of reliability of the knots. Increasing these characteristics of some knots in modified sutures allows using less complex knots in them and consequently reducing suture consumption and the risk of infection of the surgical wound.The current requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The surgical suture “Lavsan” is made by twisting of white or green polyester multifilament yarns and characterized by high strength and elasticity, good manipulation properties, and reliable surgeon's knot. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical suture “Lavsan” is made by twisting of white or green polyester multifilament yarns and characterized by high strength and elasticity, good manipulation properties, and reliable surgeon's knot. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…found that coating of the initial Lavsan sutures with a biocompatible and biodegradable polymer (polyhydroxybutyrate) did not reduce the holding power and degree of reliability of the knots. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%